Fault diagnosis based on sliding mode observer for formation of UAVs - Jun-peng SHI; Jian-wei LIU; Pu YANG; Bin JIANG (物联网学报)
Under the directed network topology,formation of UAVs with leader-follower structure was studied.And a fault estimation method using distributed adaptive sliding mode observer was designed for actuator fault with unknown upper bound.First of all,for each network node,based on the directed network topology,relative output estimation error was introduced to show information exchanges between neighbouring nodes.And a corresponding sliding mode observer was constructed.Then the global error system was defined,and the stability and sliding mode reaching condition was proved by Lyapunov theory.At last,all the parameters to be designed were calculated by the linear matrix inequality toolbox,and the validity of the proposed method was verified by Matlab simulation.